PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII3 SMP NEGERI 32 PEKANBARU - Mukhtasar, Hera Larasati; ', Zuhri; ', Kartini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aims to improve the learning process and increase the student?s mathematics learning outcomes through the implementation of Learning in Cooperative Learning of Two Stay Two Stray (TSTS). This type of research is the Classroom Action Research with two cycle. The research was conducted in class VIII3 SMP Negeri 32 Pekanbaru in the second semester of the 2016/2017 academic year with the subject of as many as 39 students.. The research instrument consists of learning devices and instrument data collectors. Learning device used in this research is the Syllabus, Lesson Plan and Worksheet. The instrument data collector used in this research is the observation sheet and math achievement test. Data analysis technique used is descriptive statistical analysis. Based on the result of the research showed that implementation of learning process on cycle II had happened improvement from implementation on cycle I. Weakness on cycle I is improved on implementation cycle II according with planning of improvement after reflection cycle I. Number of students that reach Minimum Mastery Criteria increase from basic score to daily test II. The number of students who reach Minimum Mastery Criteria on basic scor, daily test I and daily test II are respectively 15 person (38,46%), 20 person (51,28%) and 27 person (69,23%). Results of this research indicates that application of Learning in Cooperative Learning of TSTS can improve learning process and increase mathematics learning outcomes from the students at class VIII3 SMP Negeri 32 Pekanbaru in the second semester academic years 2016/2017 at Basic Competencies 4.3 Using the relationship of center angular, arc length, wide arc in solving problems, and Basic Competencies 4.4 Calculate the length of the tangent of two circle alliance.Keywords: Cooperative learning, Cooperative Learning of TSTS, student?s mathematics learning outcomes, Classroom Action Research